Differences Between Sweden and Greece in Joint Outcomes Assessed by Ultrasound in Adolescents With Severe Haemophilia on Prophylaxis : Data From the PedNet Registry - Michalopoulou, Aikaterini; Ranta, Susanna; Andersson, Nadine G.; Fischer, Kathelijn; de Kovel, Marloes; de Boer-Verdonk, Elsbeth; Motwani, Jayashree; Kenet, Gili; Pergantou, Helen (Haemophilia, 2025)
Introduction: Different strategies in prophylaxis for haemophilia among countries may affect long-term outcome. Aim: The aim of this study is to compare joint health in persons with severe haemophilia (PwSH) between Sweden and Greece, based on different approaches on prophylaxis initiation and management. Methods: Data were extracted from the PedNet Registry, which collects patient data prospectively, regarding measures on treatment and joint health using Haemophilia Joint Health Score (HJHS) and Haemophilia Early Arthropathy Detection with Ultrasound (HEAD-US). Results: Sixty-one Swedish and 51 Greek PwSH (aged ≥ 10–18 years) were included. Swedish adolescents were diagnosed at earlier age (0.53 vs. 0.77 years in Greece, p < 0.01). At prophylaxis initiation {earlier in Sweden (p < 0.01)}, dose regimens were more intense and escalation to full prophylaxis was reached earlier in Sweden. Median age at the last HEAD-US was 15.82 versus 14.07 years and at the last HJHS: 15.26 versus 15.86 years, for Sweden and Greece, respectively. Swedish and Greek PwSH had similar median total HJHS: 1.5 versus 1.0, respectively, p = 0.38. Based on HEAD-US, signs of synovitis were less frequent in Sweden for ankles (31.1% vs. 72.2%; p < 0.01), knees (11.1% vs. 44.4%, p < 0.01) and elbows (8.9% vs. 27.8%, p < 0.05). Bone/cartilage abnormalities were also less frequent in Swedish patients (ankles: 11.1% vs. 30.6%; p < 0.05, knees: 6.7% vs. 11.1%; p = 0.69, elbows: 8.9% vs. 19.4%; p = 0.20). Conclusion: Although adolescent PwSH clinically have good joint health in both countries, differences were detected by HEAD-US, with earlier prophylaxis in Sweden being associated with better joint outcomes.
Publisher Copyright: © 2025 John Wiley & Sons Ltd.
Keywords: arthropathy; haemophilia; HEAD-US; HJHS; paediatrics